2021
DOI: 10.1016/j.rx.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Manejo y seguimiento radiológico del paciente post-COVID-19

Abstract: La mayor parte de los pacientes que superan la infección por SARS-CoV-2 no presentan complicaciones ni requieren un seguimiento específico, pero una proporción significativa (especialmente aquellos con formas clínicas moderadas/graves de la enfermedad) necesitan un seguimiento clínico-radiológico. Aunque apenas existen referencias o guías clínicas sobre el seguimiento a largo plazo de estos pacientes post-COVID-19, se están realizando pruebas radiológicas y constituyendo consultas monográficas de vigilancia en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
12
0
4
Order By: Relevance
“… 2 , 17 , 18 , 19 However, the results of the present study suggest that the Δ Ψ m could also be an early indicator of multiple COVID‐19‐associated diseases, since, in recovered patients (without comorbidities with a mean time of SARS‐CoV‐2 infection of 40 ± 13 dai) of COVID‐19 present loss of mitochondrial membrane potential, a phenomenon that persisted 11 months (335 ± 20 days) after COVID‐19 infection. In this regard, some authors have reported that patients who manage to survive the effects of acute SARS‐CoV‐2 infection may develop long‐term sequelae, such as lung injury (pulmonary fibrosis), neuronal injury (acute and chronic neuropathology), and neurodegenerative diseases (Alzheimer's, Parkinson's and multiple sclerosis), 14 , 15 , 16 , 29 , 30 which could be attributed to mitochondrial dysfunction associated to SARS‐CoV‐2 infection, since it has been suggested that mitochondrial dysfunction in conjunction with an abnormal innate immunity response plays a pivotal role in the onset and development of several chronic diseases. 25 , 26 , 27 , 30 , 31 , 32 , 33…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 17 , 18 , 19 However, the results of the present study suggest that the Δ Ψ m could also be an early indicator of multiple COVID‐19‐associated diseases, since, in recovered patients (without comorbidities with a mean time of SARS‐CoV‐2 infection of 40 ± 13 dai) of COVID‐19 present loss of mitochondrial membrane potential, a phenomenon that persisted 11 months (335 ± 20 days) after COVID‐19 infection. In this regard, some authors have reported that patients who manage to survive the effects of acute SARS‐CoV‐2 infection may develop long‐term sequelae, such as lung injury (pulmonary fibrosis), neuronal injury (acute and chronic neuropathology), and neurodegenerative diseases (Alzheimer's, Parkinson's and multiple sclerosis), 14 , 15 , 16 , 29 , 30 which could be attributed to mitochondrial dysfunction associated to SARS‐CoV‐2 infection, since it has been suggested that mitochondrial dysfunction in conjunction with an abnormal innate immunity response plays a pivotal role in the onset and development of several chronic diseases. 25 , 26 , 27 , 30 , 31 , 32 , 33…”
Section: Resultsmentioning
confidence: 99%
“… 2 , 10 , 11 , 12 , 13 Patients recovering from acute SARS‐CoV‐2 infection can develop long‐term sequelae, such as lung injury (pulmonary fibrosis) and other inflammatory affections, including neurodegenerative events. 14 , 15 , 16 Thus, mitochondrial integrity is essential to maintain an adequate immune response against SARS‐CoV‐2 infection. 9 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of patients recovering from acute SARS-CoV-2 infection, they may develop long-term sequelae (pulmonary injury, inflammatory, neurodegenerative, etc.) caused by mitochondrial dysfunction [27][28][29][30][31][32][33][34]. Therefore, the search for alternative treatments is essential to reintegrate cellular homeostasis in SARS-CoV-2 infected subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear the role of the virus itself and adjuvants factors such as over-infections, far-toxicities, or mechanical ventilation. 9 Nowadays very little is known about the long-term outcome of Covid-19 infection, in particular about the permanent fibrotic changes that the virus may induce in the lung. Due to the high number of affected patients, understanding the longer-term implications is critical.…”
Section: Introductionmentioning
confidence: 99%